Marriage settlements; their social and economic effects - MacDonnell, James (Statistical and Social Inquiry Society of Ireland, 1869)
In the upper and middle ranks of society in this country the custom of settling estates is so common, that one seldom meets a person who is the absolute owner of all the property from which his income is derived. It will generally be found that a married man is tenant for life only of his estate, and unable to sell or otherwise dispose of it for any period longer than the duration of his own life. Property thus circumstanced is said to be in settlement, and the greater part of the land of this country, and a very large proportion of the public funds, are in settlement. Settlements are most commonly made on marriage, and it is to the social and economic effects of such settlements that I wish to call your attention on the present occasion.
Read, Tuesday, 26th May, 1868
Keywords: Marriage settlements in Ireland; Critique of family settlements; 314.15